INFLUENCE OF STAKEHOLDERS’ PARTICIPATION ON PERFORMANCE OF COUNTY GOVERNMENTS IN KENYA - WAIKENDA, MACHEL (INDONESIAN RESEARCH SOCIETY, 2019)
The devolved system of governance was adopted to ensure development in all regions and effectiveness in service delivery for all Kenyans. This purpose of the study was to evaluate the influence of inclusiveness of stakeholders? participation on performance of county governments in Kenya. The design methods used include the descriptive and explanatory cross-sectional survey method. The unit of analysis was the county governments. The unit of observation was county officials who included Governors, deputy Governors, County executive committee members, County secretaries, deputy County secretaries and MCAs. For this study, a sample of 354 was arrived at. Simple random sampling method was adopted for the selection of the study participants. The study used a questionnaire for collection of primary data. Data analysis was done using SPSS. Frequencies and descriptive statistics were obtained for the study?s variables and this information was presented in graphs and frequency tables. Both descriptive and inferential statistics were used. Inferential statistics included regression analysis that was used to test the significance between dependent and the independent variables. The study established that stakeholder?s participation had a significant influence on the performance of county governments in Kenya. The study concluded that inclusiveness influences the performance of county governments in Kenya significantly and positively. The study recommends that there is a need for county governments to set effective regulations through the Public Procurement Regulatory Authority so as to regulate and shape the county?s procurement procedures. This will ensure that no financial resources are unaccounted for.